Podvrste navadne dobre misli (Origanum vulgare L.) v Sloveniji - Atanasova, Lea (Natura Sloveniae, 2002)
The article discusses the taxa O. vulgare subsp. vulgare and O. vulgare subsp.viride in Slovenia. After the herbarium material was revised, distribution maps and determination key were made.
Keywords: Classification; dobra misel; Ecosystem; Ekosistem; fitogeografija; origano; Plants; prevalence; Rastline; razširjenost; Slovenia; Slovenija